The Limits and Possibilities of Philosophy: Who is the Subject of Rights in the Context of Environmental Issues? - Sedová, Tatiana; Plašienková, Zlatica (Studia Ecologiae et Bioethicae, 2026)
The authors of the paper examine the limits and possibilities of philosophy in the context of environmental issues. Philosophy cannot act as the arbiter of factual empirical problems. It cannot be the purveyor of catastrophic scenarios and romanticize the ideas of the pre-industrial age on the one hand, while acting as the prophet of technocratic optimism on the other. Doing philosophy means analysing concepts, especially ones that are essentially contested, in addition to assessing the validity of the evidence and argumentation procedures and practices relating to the contemporary ecological crisis, which is both civilizational and related to the concept of the Anthropocene. In general, philosophy should and could discuss the destructive values of consumer civilization. However, this does not mean creating a new form of mythology in which the planet acquires subjectivity. The authors critically discuss some aspects of the philosophical theory of the Czech philosopher Josef Šmajs (1938-), which attributes the cause of the contemporary ecological crisis to the flawed predatory culture and argues in favour of recognizing the subjectivity of the planet Earth and the Constitution for the Earth.